The utilization of antenatal care among rural-to-urban migrant women in Shanghai:a hospital-based cross-sectional study - Zhao Qi; Huang Zhihuan; Yang Sijia; Pan Jie; Smith Brian; Xu Biao (BMC, 2012)
Abstract Background Improving utilization of antenatal care is a critical strategy for achieving China's Millennium Development Goal of decreasing the maternal mortality ratio (MMR). While overall utilization has increased recently in China, an urban vs. rural disparity in access remains. Here we aim to assess utilization of antenatal care in rural-to-urban migrant women and identify its risk and protective factors. Methods Migrant women who had been living in Shanghai for more than six months, delivered in one of the two study hospitals between August 2009 and February 2010, and provided written consent were interviewed using a structured questionnaire. Results Of 767 women, 90.1% (691) made at least one antenatal care visit, while 49.7% (381) had adequately utilized antenatal care (i.e., made five or more antenatal care visits). Only 19.7% of women visited an antenatal care center during the first trimester (12 weeks). Women between the ages of 25 and 30 and women older than 30 were more likely than younger women to have adequately utilized antenatal care (AOR=2.2 and 1.9, 95%CI=1.4-3.5 and 1.1-3.2, respectively). Women whose husbands held Shanghai residency status (AOR=4.9, 95%CI=2.2-10.9) or who had more than 10 years of education (AOR=1.8, 95%CI=1.2-2.9), previously experienced a miscarriage or abortion (AOR=2.2, 95%CI=1.3-3.8), had higher household income (AOR=1.6, 95%CI=1.0-2.5) were more likely to have adequately utilized antenatal care. Women from high-income households were also more likely to receive antenatal care during the first 12 weeks (AOR=3.5, 95%CI=1.7-5.5). Conclusions Many migrant women in Shanghai did not receive adequate antenatal care and initiated antenatal care later than the optimal first 12 weeks of pregnancy. Poor antenatal care utilization was associated with low socioeconomic status, education, and certain demographic factors. Tailored health education for both migrant women and their husbands should be strengthened to improve maternal health. Financing supports should be provided to improve the utilization of antenatal care.